Entrepreneurial Abilities and Business Performance: Enacting Business Survival Paradigm from Electronics Informal Market, Nigeria - Adebanji Adejuwon William Ayeni (World, 2025)
In today’s evolving society, meaningful development cannot be fully realized without acknowledging the vital role of the electronics sector, especially as it functions within informal markets. These markets have become more than just centers of commerce; they serve as informal learning grounds where many young people acquire entrepreneurial skills, develop resilience, and find alternatives to social vices. For many, informal entrepreneurship is not just an option but a means of survival and self-empowerment. Despite their growing relevance, the link between the entrepreneurial abilities nurtured in these informal markets and actual business performance has not been adequately examined. This study, therefore, aimed to explore how informal electronics entrepreneurs in a developing economy navigate their environment, overcome challenges, and create wealth through vision, innovation, and calculated risk-taking. Anchored in institutional theory, the research employed a qualitative approach, using cluster, purposive, and simple random sampling to select participants from key informal business units. Interviews were conducted, transcribed, and analyzed using QSR NVivo 12, allowing for deep insight into the lived experiences of the entrepreneurs. Findings revealed that 78% of participants emphasized practical suggestions that aid informal business survival, such as customer-driven innovations, adaptive strategies, and avoiding confrontations with regulatory agencies. Key attributes such as foresight, adaptability, and risk management accounted for 66% of the variance in corporate success. Strategic and innovative approaches are enabling informal firms to endure and prosper, since 61% of respondents associated these competencies with organizational success. The new BSP framework, which integrates institutional and contingency theories, illustrates how informal enterprises endure by conforming to or opposing institutional pressures and adjusting to environmental changes. The results indicate that, when properly understood and supported, the informal electronics sector may develop sustainably. This study demonstrates that informal entrepreneurship is influenced by formal regulations, informal norms, and local enforcement mechanisms, therefore enhancing institutional theory and elucidating business behavior in developing nations. The Business Survival Paradigm [BSP] illustrates how informal enterprises navigate institutional obstacles to endure. It advocates for policies that integrate the official and informal sectors while fostering sustainable development. The paper advocates for ongoing market research to assist informal firms in remaining up-to-date. It implores authorities to acknowledge the innovative potential of the informal sector and to provide supportive frameworks for sustainable growth and formal transition where feasible.